Pic Protein From Enteroaggregative E. coli Induces Different Mechanisms for Its Dual Activity as a Mucus Secretagogue and a Mucinase - Flores-Sanchez, Fernando; Chavez-Dueñas, Lucia; Sanchez-Villamil, Javier; Navarro-Garcia, Fernando (Frontiers in Immunology, 2020)
A hallmark of enteroaggregative Escherichia coli (EAEC) infection is the formation of an intestinal biofilm, which comprises a mucus layer with immersed bacteria. Pic is an autotransporter secreted by EAEC, and other E. coli pathotypes, and has been involved in two apparently contradictory phenotypes, as a mucus secretagogue and as a mucinase. Here, we investigated this Pic dual activity, mucus secretagogue capability and mucinolytic activity, in human goblet cells that secrete MUC2 and MUC5AC. Pic induced mucus hypersecretion directly in the goblet cells, without other intestinal cell types involved. At the same time, Pic exhibited strong proteolytic activity on the secreted mucins. These activities were independent since a mutation in the serine protease motif (PicS258I) abolished mucin degradation while maintaining the mucus secretagogue activity intact. Furthermore, deoxycholic acid (DCA)-induced mucins were proteolytically degraded when goblet cells were co-incubated with DCA/Pic, while co-incubation with DCA/PicS258I induced a synergistic effect on mucus hypersecretion. Pic was more efficient degrading MUC5AC than MUC2, but no degradation was detected with Pic inactivated at the active site by mutation or pharmacological inhibition. Remarkably, Pic cleaved MUC2 and MUC5AC in the C-terminal domain, leaving N-terminal subproducts, impacting the feature of gel-forming mucins and allowing mucus layer penetration by EAEC. Astonishingly, Pic stimulated rapid mucin secretion in goblet-like cells by activating the intracellular calcium pathway resulting from the PLC signal transduction pathway, leading to the production of DAG and releasing IP3, a second messenger of calcium signaling. Therefore, the dual activity of Pic, as a mucus secretagogue and a mucinase, is relevant in the context of carbon source generation and mucus layer penetration, allowing EAEC to live within the layer of mucus but also access epithelial cells.